The corvitini role in the corrections disturbances of proteinase inhibitors system in blood under conditions of the development of experimental bacterial keratitis on the background of experimental bronchial asthma and pneumonia - Kravets, B. B. (Journal of Education, Health and Sport, 2015)
Kravets B. Роль корвітину в корекції порушених показників протеїназо-інгібіторної системи в крові за умов розвитку експериментального бактеріального кератиту на тлі експериментальної бронхіальної астми і пневмонії = The corvitini role in the corrections disturbances of proteinase inhibitors system in blood under conditions of the development of experimental bacterial keratitis on the background of experimental bronchial asthma and pneumonia. Journal of Education, Health and Sport. 2015;5(10):141-145. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.32529 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2810%29%3A141-1455 https://pbn.nauka.gov.pl/works/660616 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2015. Revised 05.09.2015. Accepted: 20.10.2015. УДК: 617.713 – 002 – 002+616.24 – 002 +616.248) –092.4/.9 – 02:616.153.1] –085.274 Роль корвітину в корекції порушених показників протеїназо-інгібіторної системи в крові за умов розвитку експериментального бактеріального кератиту на тлі експериментальної бронхіальної астми і пневмонії The corvitini role in the corrections disturbances of proteinase inhibitors system in blood under conditions of the development of experimental bacterial keratitis on the background of experimental bronchial asthma and pneumonia Б. Б. Кравець B. Kravets Львівський національний медичний університет імені Данила Галицького Danylo Halytskyi Lviv National Medical University Resume In research on the 21 days of experiment was found imbalance of the proteolysis equilibrium (increases level in the blood of azoalbumini, azokaseini, azocolageni ) and inhibitors system (decrease in the blood of the α2 macroglobulin and α1 inhibitor protease). The decrease products of azoalbumini, azokaseini, azocolageni and increasing of α2 macroglobulin and α1 inhibitor protease in the blood of experimental guineas pigs was found after using of corvitini compared to the untreated animals on the 21 days. Key words: bacterial keratitis, bronchial asthma, pneumonia. Резюме У роботі наведено порушення рівноваги протеолізу (підвищення вмісту в крові азоальбуміну, азоказеїну, азоколагену) та інгібіторної системи (зниження α2 макроглобуліну і α1 інгібітору протеаз в крові), особливо на 21-шу добу експерименту та зниження показників азоальбуміну, азоказеїну, азоколагену і підвищення α2 макроглобуліну і α1 інгібітору протеаз в крові морських свинок після застосування корвітину в порівнянні з нелікованими тваринами на 21-шу добу експерименту. Ключові слова: бактеріальний кератит, бронхіальна астма, пневмонія.